Recent Advances in Intelligent Control Systems - Yu, Wen (Springer London : Imprint: Springer, 2009)
Intelligent control - control based on fuzzy logic and neural networks - has changed the face of industrial control engineering whether in terms of autonomous spacecraft operation, exploratory robots or increasing the profitability of mineral-processing or steel-rolling plants. Recent Advances in Intelligent Control Systems gathers contributions from workers around the world and presents them in four categories according to the style of control employed: fuzzy control; neural control; fuzzy neural control; and intelligent control. The contributions illustrate the interdisciplinary antecedents of intelligent control and contrast its results with those of more traditional control methods. A variety of design examples, drawn primarily from robotics and mechatronics but also representing process and production engineering, large civil structures, network flows, and others, provide instances of the successful application of computational intelligence for control. Presenting state-of-the-art research, this collection will be of significant benefit to researchers in automatic control, automation, computer science (especially artificial intelligence) and mechatronics while graduate students and practicing control engineers working with intelligent systems will find it a good source of study material.